PERBANDINGAN UJI SENSITIVITAS CEFTRIAXONE DAN CEFOXITIN TERHADAP STREPTOCOCCUS ????- HEMOLYTICUS PADA PEROKOK - NUR HALIZA RASYID; ANCE ROSLINA (JURNAL ILMIAH SIMANTEK, 2021)
Exposure to tobacco smoke in cigarettes can increase the risk of respiratory tract infections due to Group A Streptococcusbeta hemolyticus. The treatments use broad spectrum antibiotics including cephalosporins. This study aims to determine thesensitivity test of ceftriaxone and cefoxitin to Streptococcus β-hemolyticus in smokers. This study uses analytic observationaldesign and fulfil the exclusion and inclusion criteria by purposive sampling. The number of samples are 25 smoker's throatswab samples that were gram stained, cultured in muller hinton and blood agar, as well as ceftriaxone and cefoxitin antibiotictests. Data was processed using Mann- Whitney test and T test. The results of research conducted by the unpaired T test onceftriaxone antibiotics obtained p = 0.003 (<0.05). The unpaired T test on cefoxitin antibiotics obtained p = 0.378 (<0.05).The value of ceftriaxone antibiotic sensitivity is greater than the cefoxitin antibiotic against Streptococcus β-hemolyticusbacteria.